Shifts in metabolic hydrogen sinks in the methanogenesis-inhibited ruminal fermentation: a meta-analysis - Ungerfeld, Emilio M. (Frontiers in Microbiology, 2015)
Maximizing the flow of metabolic hydrogen ([H]) in the rumen away from CH4 and towards volatile fatty acids (VFA) would increase the efficiency of ruminant production and decrease its environmental impact. The objectives of this meta-analysis were: i) To quantify shifts in metabolic hydrogen sinks when inhibiting ruminal methanogenesis in vitro; and ii) To understand the variation in shifts of metabolic hydrogen sinks among experiments and between batch and continuous cultures systems when methanogenesis is inhibited. Batch (28 experiments, N=193) and continuous (16 experiments, N=79) culture databases of experiments with at least 50% inhibition in CH4 production were compiled. Inhibiting methanogenesis generally resulted in less fermentation and digestion in most batch culture, but not in most continuous culture, experiments. Inhibiting CH4 production in batch cultures resulted in redirection of metabolic hydrogen towards propionate and H2 but not butyrate. In continuous cultures, there was no overall metabolic hydrogen redirection towards propionate or butyrate, and H2 as a proportion of metabolic hydrogen spared from CH4 production was numerically smaller compared to batch cultures. Dihydrogen accumulation was affected by type of substrate and methanogenesis inhibitor, with highly fermentable substrates resulting in greater redirection of metabolic hydrogen towards H2 when inhibiting methanogenesis, and some oils causing small or no H2 accumulation. In both batch and continuous culture, there was a decrease in metabolic hydrogen recovered as the sum of propionate, butyrate, CH4 and H2 when inhibiting methanogenesis, and it is speculated that as CH4 production decreases metabolic hydrogen could be increasingly incorporated into formate, microbial biomass, and, perhaps, reductive acetogenesis in continuous cultures. Energetic benefits of inhibiting methanogenesis depended on the inhibitor and its concentration and on the in vitro system.